Vernetzte Fertigung - Berücksichtigung der Herstellungshistorie von Blechbauteilen beim Fügen durch Umformen - Wiesenmayer, Sebastian; Heyser, Per; Nehls, Thomas; Frey, Philipp; Flügge, Wilko; Meschut, Gerson; Merklein, Marion (wt Werkstattstechnik - Online, 2020)
Sheet metal components are manufactured in various cutting and forming operations influencing the resulting properties of the parts. As these properties differ from the initial state of the semi-finished products, they have to be considered in the design of clinched joints. By connecting individual processes, this paper presents an approach for determining the properties of semi-finished parts in shear-cutting operations as well as their effects on the joint quality in clinching.